Post-modern culture industry management: new paradigm of culture geopolitics (Economic and Political Thought, 2018)
Culture is one of the social and common results of the process of creatingreality. According to Luckmann and Berger theory of social constructionism,it is a state of constant transmission of knowledge and an effect of multipliedreinterpretation of the surroundings. At present, the flow of informationis an element constructing culture. Every beam carries a message identifiedthrough the prism of language, tradition, values and symbolism. Onebecomes a consumer of culture taking part in other life-related transactions.The culture of global flows is a phenomenon with no clear source, with notraditionally identified sender. Contemporary forms of communication moreand more often push the content of a message to the margin of significance.As a consequence, we observe the effect of culture trivialisation (a phenomenonof infotainment) included in the category of industry: a concept variationintroduced by Horkheimer and Adorno in Dialectic of Enlightenment. Industrypushes authors away as it stands in opposition to the vanguard. The productsof culture take part in competition and fight for funding. Maintaining artisticindependence in mercantile surroundings becomes more and more difficult.Market success is proportionally correlated with the cultural level of brandsignificance a carrier of a particular message. Anticipating customers’ (consumers’)needs, it is necessary to take into consideration economic factors,however, creating culture, which is the clue of the whole process. In case ofpublic patronage, funding culture, the state implements its own objectives,often those of a given political party. It should be taken into considerationthat culture is the most stable unifying force and it is most difficult to changeit. It is not possible to leave a culture family as a result of a single politicaldecision. Level, quality, cultural achievements of a nation, society (the state)determines the geopolitical position.
Keywords: culture industry, geopolitics, patronage, vanguard, image, creation, global flows of significance